EVALUATING SISDM EFFECTIVENESS USING THE EUCS METHOD: A CASE STUDY AT SSDM POLRI - Ahmadin Cetta Subagyo; Nurul Khasanah (Jurnal Pilar Nusa Mandiri, 2026)
The Human Resource Information System (SiSDM) application of the Indonesian National Police (Polri) serves as a digital tool to support personnel management. The success of its implementation strongly depends on user satisfaction. This study aims to analyze the effectiveness of the SiSDM system using the End-User Computing Satisfaction (EUCS) method, which consists of five key dimensions: content, accuracy, format, ease of use, and timeliness. A quantitative research method was applied by distributing questionnaires to 100 personnel at SSDM Polri who actively use the SiSDM application. The collected data were analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique with the help of SmartPLS software. The results indicate that format, accuracy, and timeliness have a significant influence on user satisfaction, while content and ease of use do not show a significant effect. The R² value of 0.810 reveals that 81% of the variance in user satisfaction can be explained by the five EUCS dimensions, with f² values indicating that most dimensions contribute substantially to user satisfaction. This research confirms that the EUCS method is effective for evaluating information system quality in government institutions such as Polri. In practical terms, these insights provide input for the Indonesian National Police to prioritize improvements in format, accuracy, and timeliness, as well as to improve content and ease of use so that the system better meets the needs of personnel. As a result, the ongoing development of SiSDM can support organizational performance improvement, information transparency, and HR management efficiency within the Indonesian National Police.